A Universal Strategy toward the Precise Regulation of Initial Coulombic Efficiency of Li‐Rich Mn‐Based Cathode Materials. Issue 38 (1st August 2021) - Guo, Weibin; Zhang, Chenying; Zhang, Yinggan; Lin, Liang; He, Wei; Xie, Qingshui; Sa, Baisheng; Wang, Laisen; Peng, Dong‐Liang
Abstract: Li‐rich Mn‐based cathode materials (LRMs) are potential cathode materials for high energy density lithium‐ion batteries. However, low initial Coulombic efficiency (ICE) severely hinders the commercialization of LRM. Herein, a facile oleic acid‐assisted interface engineering is put forward to precisely control the ICE, enhance reversible capacity and rate performance of LRM effectively. As a result, the ICE of LRM can be precisely adjusted from 84.1% to 100.7%, and a very high specific capacity of 330 mAh g −1 at 0.1 C, as well as outstanding rate capability with a fascinating specific capacity of 250 mAh g −1 at 5 C, are harvested. Theoretical calculations reveal that the introduced cation/anion double defects can reduce the diffusion barrier of Li + ions, and in situ surface reconstruction layer can induce a self‐built‐in electric field to stabilize the surface lattice oxygen. Moreover, this facile interface engineering is universal and can enhance the ICEs of other kinds of LRM effectively. This work provides a valuable new idea for improving the comprehensive electrochemical performance of LRM through multistrategy collaborative interface engineering technology. Abstract : Introduced cation/anion double defects can reduce the interface charge transfer resistance and enhance the Li + ion diffusion coefficient. The induced in situ surface reconstruction layer can increase the electronic conductivity and stabilize the surface lattice oxygen. As a result, the initial Coulombic efficiency of Li‐rich Mn‐based cathode material is controlled precisely.